Uji Beberapa Dosis Biofungisida Berbahan Aktif Trichoderma Koningii Rifaii terhadap Penyakit Virus Kompleks, Pertumbuhan dan Hasil Tanaman Tomat (Lycopersicum Esculentum Mill.) - Dirga Rahmad Effendi; Muhammad Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The research aims to obtain the best dose of biofungicide containing Trichoderma koningii Rifaii. to increase the resistance of tomatoes plants to virus complex and to study it’s effect on the growth and yield of tomatoes plants. This research has been conducted at the Laboratory of Plant Pathology and Experimental Field Screen House, Faculty of Agriculture, University of Riaufor five months from November 2017 to Maret 2018. The reserch was conducted experimentally, arranged in a completely randomized design, consisting of 4 treatments (25, 50, 75, 100 gram of biofungicide ) and 5 replications. Data were analyzed statistically with analysis of variance and the means of each treatment was compared by using Duncan’s New Multiple Range Test (DNMRT) at 5% level. The result showed that the doses of biofungicide of T. koningii had different effect on the first time of symptom appeared disease intensity, plant growth and yield. Biofungicide of T. koningii at 75 gram of biofungicide tender to a better ability to control the virus complex disease, increase the growth and yield of tomatoes plants.Keywords :Biofungicide, Trichoderma koningii, virus complex disease, tomatoes plants.